2016
DOI: 10.1161/hypertensionaha.115.06305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management and Outcomes of Adrenal Hemorrhage Following Adrenal Vein Sampling in Primary Aldosteronism

Abstract: Aldosterone-producing adenoma and bilateral adrenal hyperplasia account for >90% of all primary aldosteronism cases. Distinguishing between bilateral and unilateral disease is of fundamental importance because it allows targeted therapy. Adrenal vein sampling (AVS) is the only reliable means to preoperatively differentiate between unilateral and bilateral subtypes. A rare but serious complication of AVS is an adrenal hemorrhage (AH). We retrospectively examined in detail 24 cases of AH during AVS in 6 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 24 publications
0
40
1
2
Order By: Relevance
“…The left adrenal vein is usually easily cannulated, because it generally drains directly into the left renal vein [49], while the cannulation of the shorter and smaller right adrenal vein, which usually drains directly into the inferior vena cava, can be difficult. Despite being a challenging procedure, the complication rate associated with AVS is very low (0.61%) [20]; adrenal haemorrhage, which is the most serious complication, has a favourable outcome in the majority of patients, causing minor or no permanent effects on adrenal function [50]. Other AVS protocols are described below.…”
Section: Avs Methodologymentioning
confidence: 99%
“…The left adrenal vein is usually easily cannulated, because it generally drains directly into the left renal vein [49], while the cannulation of the shorter and smaller right adrenal vein, which usually drains directly into the inferior vena cava, can be difficult. Despite being a challenging procedure, the complication rate associated with AVS is very low (0.61%) [20]; adrenal haemorrhage, which is the most serious complication, has a favourable outcome in the majority of patients, causing minor or no permanent effects on adrenal function [50]. Other AVS protocols are described below.…”
Section: Avs Methodologymentioning
confidence: 99%
“…In instances where AVS lateralization data are successfully acquired, if the AH affects the contralateral adrenal to an APA, one may question whether surgically removing the adrenal with the APA will render the patient adrenally insufficient (Figure ). As demonstrated by Monticone and colleagues, only one case of adrenal insufficiency was encountered in such a scenario, suggesting that this is a rare occurrence. However, because of the limited sample size, one cannot make definitive conclusions.…”
Section: Management Of Pa Post Ahmentioning
confidence: 89%
“…The investigators also found that AH was inversely correlated with the number of procedures performed by each radiologist . In another study that primarily explored the management and outcomes of AH during AVS, Monticone and colleagues reported 24 cases of PA with AH from six different centers. AH occurred more frequently (n=18 of 24) in the right adrenal vein, in keeping with previously published reports .…”
Section: Management Of Pa Post Ahmentioning
confidence: 98%
See 2 more Smart Citations